2012
DOI: 10.1073/pnas.1214019109
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor 1-dependent expression of platelet-derived growth factor B promotes lymphatic metastasis of hypoxic breast cancer cells

Abstract: Lymphatic dissemination from the primary tumor is a major mechanism by which breast cancer cells access the systemic circulation, resulting in distant metastasis and mortality. Numerous studies link activation of hypoxia-inducible factor 1 (HIF-1) with tumor angiogenesis, metastasis, and patient mortality. However, the role of HIF-1 in lymphatic dissemination is poorly understood. In this study, we show that HIF-1 promotes lymphatic metastasis of breast cancer by direct transactivation of the gene encoding pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
167
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(174 citation statements)
references
References 39 publications
6
167
1
Order By: Relevance
“…As discussed in detail in section 2.1., in mice bearing breast cancer orthografts, digoxin was reported to block lymphangiogenesis and lymphatic metastases to a similar extent as PDGFRβ inhibition by imatinib [36]. Interestingly, xenografts derived from cells with HIF-1α enforced expression were resistant to the anti-tumor effect of digoxin, showing that HIF-1α is the critical target of digoxin for cancer therapy [172].…”
Section: Tentative Treatment Perspectives On the Crossroad Of Hif-rtkmentioning
confidence: 99%
See 4 more Smart Citations
“…As discussed in detail in section 2.1., in mice bearing breast cancer orthografts, digoxin was reported to block lymphangiogenesis and lymphatic metastases to a similar extent as PDGFRβ inhibition by imatinib [36]. Interestingly, xenografts derived from cells with HIF-1α enforced expression were resistant to the anti-tumor effect of digoxin, showing that HIF-1α is the critical target of digoxin for cancer therapy [172].…”
Section: Tentative Treatment Perspectives On the Crossroad Of Hif-rtkmentioning
confidence: 99%
“…This second mechanism is indirectly mediated by the HIF system, too. In breast cancer cells, it was specifically shown that HIF-1α binds to a site in intron 3 of the PDGF-B gene to activate its transcription [36]. The PDGF family consists of disulfide-bonded homodimers of A-, B-, C-and D-polypeptide chains as well as the heterodimer PDGF-AB.…”
Section: Induction Of Rtk Ligandsmentioning
confidence: 99%
See 3 more Smart Citations